Cultura negra em Alagoas: uma construção de negritude - Silva, Jeferson Santos da (2008)
Ethnicity and identity are very controversial issues in Brazil because of the debate on adoption of public policies which has in the race its support criteria. Such debate is not new, neither the classification practice with basis on ethnic features. In this essay, we intend scrutinize how some black organization from Alagoas build and verbalize their blackness. Such blackness has an important influence from the Salvador s black culture in it definition about what is being black to those organizations. We perceived that is not a mere copy, but a way in which alagoanos black segments externalize their culture as well, with aim to be better accept by the local society as well as happen in all the country with the black organizations in Salvador. It process built a self affirmation pattern that practically ignore it local culture whereas adopt the baiana afro-referenciality. In this chapter we still sought to analyze how State intervention interfere on the black culture s definition as well as we established a dialogue between alagoano black movement militants and theoreticals that broached black identity in theirs studies. Such theoreticals pray the idea of a displaced person (self) despite of racism define in a very precise way, the place that the Negro fill. We still built a critic on the way that black movement do its politics because its speech is full of racist ideology elements. On the other hand, we perceived the necessity that the movement has in keep its speech because is as Negro that the society build them